ARENIG (MIDDLE ORDOVICIAN) OSTRACODS FROM BALTOSCANDIA: FAUNA, ASSEMBLAGES AND BIOFACIES - Tinn O.; Meidla T.; Ainsaar L. (My University, 2006)
The Arenig ostracod fauna of Baltoscandia is the oldest known and amongst the most thoroughly studied ostracod faunas in the world. The fauna is dominated by eridostracans and palaeocopes, and comprises altogether about fifty species from seven suborders. The ten most abundant ostracod species make up 90% of the total Arenig fauna. Overall ostracod diversity estimates in the Arenig of the Baltoscandian Palaeobasin are low, but show gradual increase in diversity at younger horizons. Low diversity may be due to unfavourable climate conditions in the Baltoscandian Palaeocontinent during the earlier Arenig and may also be due to the early stage of evolution of ostracod faunas (i.e. pre their main diversification during the Llanvirn). Thirteen facies related Arenig ostracod assemblages are distinguished in the Baltoscandian Palaeobasin. In early- and mid-Volkhov time, the assemblages show almost basinwide distribution suggesting many ostracod species were environmental generalists. Major distinctions between different ostracod biofacies zones can be seen from the late Volkhov onwards, when the differentiation of ostracod biofacies in the Palaeobasin marks the onset of major depth differences. Ostracod assemblage-based reconstruction of sea-level changes in the studied area agrees well with the sequence stratigraphic interpretation of the succession and with a sea level curve determined on the basis of sedimentological data.
Keywords: Ordovician; Paleozoic::Ordovician; Палеозой::Ордовикская